The G(i)-coupled P2Y12 Receptor Regulates Diacylglycerol-mediated Signaling in Human Platelets - Guidetti, Gianni F. (American Society for Biochemistry and Molecular Biology, 2008)
Stimulation of G(q)-coupled receptors activates phospholipase C and is supposed to promote both intracellular Ca(2+) mobilization and protein kinase C (PKC) activation. We found that ADP-induced phosphorylation of pleckstrin, the main platelet substrate for PKC, was completely inhibited not only by an antagonist of the G(q)-coupled P2Y1 receptor but also upon blockade of the G(i)-coupled P2Y12 receptor. The role of G(i) on PKC regulation required stimulation of phosphatidylinositol 3-kinase rather than inhibition of adenylyl cyclase. P2Y12 antagonists also inhibited pleckstrin phosphorylation, Rap1b activation, and platelet aggregation induced upon G(q) stimulation by the thromboxane A(2) analogue U46619. Importantly, activation of phospholipase C and intracellular Ca(2+) mobilization occurred normally. Phorbol 12-myristate 13-acetate overcame the inhibitory effect of P2Y12 receptor blockade on PKC activation but not on Rap1b activation and platelet aggregation. By contrast, inhibition of diacylglycerol kinase restored both PKC and Rap1b activity and caused platelet aggregation. Stimulation of P2Y12 receptor or direct inhibition of diacylglycerol kinase potentiated the effect of membrane-permeable sn-1,2-dioctanoylglycerol on platelet aggregation and pleckstrin phosphorylation, in association with inhibition of its phosphorylation to phosphatidic acid. These results reveal a novel and unexpected role of the G(i)-coupled P2Y12 receptor in the regulation of diacylglycerol-mediated events in activated platelets.